2020
DOI: 10.3390/s20216124
|View full text |Cite
|
Sign up to set email alerts
|

Active Disturbance Rejection Position Synchronous Control of Dual-Hydraulic Actuators with Unknown Dead-Zones

Abstract: In this paper, an integrated control strategy of position synchronization control for dual-electro-hydraulic actuators with unknown dead-zones is proposed. The unified control scheme consists of two parts: One is adaptive dead-zone inverse controllers of each hydraulic actuator to offset the unknown dead-zones. The other is the linear active disturbance rejection controller (LADRC) for position synchronization error. First, the model of the electro-hydraulic proportional position control system (EPPS) was iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Among these algorithms, the PSO is the most popular among many intelligent algorithms due to its simple structure, easy implementation and minor code. This algorithm is proposed by Kennedy and Eberhart in 1995, inspired by bird swarm motion [41], and has been successfully applied to many control fields [42][43][44][45]. For instance, in [42], an ADRC of an induction motor is proposed based on a particle swarm optimization (PSO) algorithm to realize the precise decoupling of the induction motor and the disturbance compensation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these algorithms, the PSO is the most popular among many intelligent algorithms due to its simple structure, easy implementation and minor code. This algorithm is proposed by Kennedy and Eberhart in 1995, inspired by bird swarm motion [41], and has been successfully applied to many control fields [42][43][44][45]. For instance, in [42], an ADRC of an induction motor is proposed based on a particle swarm optimization (PSO) algorithm to realize the precise decoupling of the induction motor and the disturbance compensation.…”
Section: Introductionmentioning
confidence: 99%
“…In [43], the XK-I spherical robot PSO-ADRC motion controller with parameter tuning function is designed by combining the state equation with PSO algorithm. The PSO algorithm is improved by using the genetic algorithm theory to improve the optimization range and convergence rate of the algorithm, and the parameters of the ADRC were adjusted online [45]. However, due to the problems of gradually losing population diversity, falling into local extremum, and low accuracy in the application process of particle swarm optimization, scholars have proposed various improvement measures.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the method can maintain the synchronous accuracy of the double hydraulic cylinders between 0 and 0.66 mm under the condition of satisfying the working requirements of the scissor lift mechanism. Wang et al [24] proposed an integrated control strategy for the position synchronization control of dual electrohydraulic actuators with unknown dead zones. Li et al [25] proposed a design scheme for the mechanical structure of the synchronous precision control of a double-cylinder gantry hydraulic machine.…”
Section: Introductionmentioning
confidence: 99%
“…The internal factors are the inherent characteristics of the electrohydraulic system that the regulation of which will not change for a very long time until some parts of the system are failed, including dead zone, hysteresis, friction, and so forth. [11][12][13] Therefore, the models of these internal factors can be obtained by repetitive experiments or some analyzing algorithms. That means a model-based controller can be easily designed to compensate the effect that whatever internal factors bring into the system.…”
Section: Introductionmentioning
confidence: 99%